PERSEPSI MASYARAKAT TENTANG PEMBANGUNAN DI JORONG SIRAHO DAN JORONG SUNGAI KAPUR NAGARI LUBUK KARAK KECAMATANIX KOTO KABUPATEN DHARMASRAYA - Markasia, Yuni - (STKIP PGRI Sumbar, 2014)
The purpose of research are to get data, to process, to analize, to discuss and to know perception of society about development in Jorong Siraho and Jorong Sungai Kapur Nagari Lubuk Karak, IX Koto subdistrict, Dharmasraya regency account for : 1) Communication network, 2) Transportation facilities and 3) Street development. The kind of research is descriptive. The population of research is the grade of patriarch in Jorong Siraho and Jorong Sungai Kapur Nagari Lubuk Karak, IX Koto subdistrict, Dharmasraya regency amounted to 114 patriarch. The sample af research has taken with proportional random sampling technique with 50 % proportion sample amounten to 56 patriarch. The result of research indicate that: 1) Perception of society about communication network development is fairly well cause society could be filling the bill life especially of information requirement sector, 2) Perception of society about transportation facilities development is fairly well cause society use motorcycle with ownership. Not to speak of there are a portion of society use common carrier to carry agricultural produce, 3) Perception of society about street development is fairly well although street has through everyday pebble and rarely has through vehicle like car, street that will be repairable by development by and large asphalt with street development has thereâs been to help society in agricultural produce transport.